1977
DOI: 10.1128/jb.130.1.74-81.1977
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of arylsulfatase synthesis in Klebsiella aerogenes

Abstract: It was shown that at least four genes are specifically responsible for arylsulfatase synthesis inKlebsiella aerogenes. Mutations at chromosome site atsA result in enzymatically inactive arylsulfatase. Mutants showing constitutive synthesis of arylsulfatase (atsR) were isolated by using inorganic sulfate or cysteine as the sulfur source. Another mutation in which repression of arylsulfatase by inorganic sulfate or cysteine could not be relieved by tyramine was determined by genetic analysis to be on the tyramin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 18 publications
(30 reference statements)
3
38
0
Order By: Relevance
“…The syntheses ofboth enzymes were repressed when the cells were grown on glucose with ammonium chloride even in the presence of tyra- (2,9).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The syntheses ofboth enzymes were repressed when the cells were grown on glucose with ammonium chloride even in the presence of tyra- (2,9).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the genetic regulation of arylsulfatase synthesis, we chose K. aerogenes W70, since E. coli K-12 and S. typhimurium LT2, the bacterial strains most widely used in genetic analyses, produce little or no arylsulfatase under normal conditions. On the basis of genetic studies using the general transducing phage PW52 and introducing the coliphage P1 or F' episomes into K. aerogenes, we proposed a model of genetic regulation of arylsulfatase synthesis (9). Furthermore, in immunological studies we showed that there is a similar regulation system of arylsulfatase synthesis in enteric bacteria (12,21) and in intergeneric hybrid strains between K. aerogenes and E. coli or S. typhimurium (11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations